Enabling Smart Governance: SIPRAJA Service System Implementation - Agustin, Nailul Isnaini; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the implementation of SIPRAJA as a manifestation of smart governance in the administration of Suko Village, Sidoarjo Sub-district, Sidoarjo Regency. Employing a descriptive research design with qualitative methodology, data were collected through interviews, documentation, and observation. Findings reveal key aspects for improvement, notably in communication among RT RW entities for more effective dissemination of information to the community. However, the human resource, infrastructure, and disposition factors within SIPRAJA in Sidoarjo Sub-district align effectively with the objectives set by the local government. The village officials in Suko demonstrate optimal performance in service delivery, exhibiting friendly attitudes and assisting residents unfamiliar with the SIPRAJA application. Additionally, the bureaucratic structure ensures clear task allocation and service responsibilities, exemplified by the Village Head's management and the SOP that ensures the issuance of documents without charge, obtainable directly at the village government office. This study underscores the need for enhanced communication strategies while highlighting the successful alignment of resources and bureaucratic structure toward efficient service provision, ultimately advancing the discourse on smart governance implementations in rural settings. Highlights: Improved Communication: Addressing gaps in information dissemination among local entities (RT RW) crucial for community engagement. Efficient Service Provision: Effective utilization of human resources and infrastructure aligned with government objectives. Transparent Bureaucratic Processes: Clear task allocation and SOP ensuring cost-free document issuance, enhancing accessibility for residents. Keywords: Smart Governance, SIPRAJA, Rural Administration, Service Delivery, Bureaucratic Structure